No Alteration of Optical Coherence Tomography and Multifocal Visual Evoked Potentials in Eyes With Symptomatic Carotid Artery Disease - Lee, John-Ih; Gemerzki, Lena; Boerker, Laura; Guthoff, Rainer; Aktas, Orhan; Gliem, Michael; Jander, Sebastian; Hartung, Hans-Peter; Albrecht, Philipp (Frontiers in Neurology, 2019)
Background: Symptomatic carotid artery disease (CAD) may cause modified blood supply to the retina possibly leading to retinal structure changes. Results of previous studies in asymptomatic CAD were heterogeneous in retinal layer changes measured by OCT. The objectives of this prospective, non-interventional study were to investigate if structural retinal changes occur in symptomatic CAD patients with macroangiopathic ischemic stroke or transient ischemic attack (TIA). Methods: We used spectral-domain optical coherence tomography (SD-OCT) to cross-sectionally and longitudinally analyze the retinal morphology of CAD patients with macroangiopathic ischemic stroke or TIA not permanently affecting the visual pathway. We employed semi-automated segmentation of macular volume scans to assess the macular retinal layers' thickness and peripapillary ring scans to determine the peripapillary retinal nerve fiber layer thickness using the contralateral eye and eyes of microangiopathic ischemic stroke patients with matched age, gender, and vascular risk factors as control. Visual function and visual field deficits were assessed by multifocal visual evoked potentials (mfVEP). Results: Neither the thickness of retinal layers measured by SD-OCT in 17 patients nor the mfVEP latency or amplitude in 10 patients differed between the symptomatic stenotic, the contralateral internal carotid artery (ICA) side and the control group of 17 microangiopathic stroke patients at baseline. Furthermore, longitudinal investigations of 10 patients revealed no significant changes of any retinal layer 4 months after ischemic stroke or TIA. Conclusion: In conclusion, our study revealed no evidence for an impact of symptomatic carotid artery disease on retinal structure or functional impairment of the visual pathway.